KNOWLEDGE AND PRACTICES OF HEALTH ASSISTANT NURSING TECHNICAINS TOWARDS PATIENT SAFETY IN SAUDI HOSPITALS: A CROSS-SECTIONAL STUDY - Muhammad Al-Aswad Eid Al-Mutairi, Muhammad Dhiab Radaan Al-Mutairi, Muhammad Abdullah Eid Al-Mutairi, Hamad Abdullah Jailan Al-Mutairi, Sattam Al-Humaidi Rafidan Al-Mutairi, Talal Fayez Rafidan Al-Mutairi (Chelonian Research Foundation, 2022)
Background: Patient safety is a critical aspect of healthcare delivery, and nursing technicains play a vital role in promoting a culture of safety in clinical settings. This study aimed to assess the knowledge and practices of health assistant nursing technicains towards patient safety in Saudi hospitals. Methods: A cross-sectional study design was used to collect data from 385 health assistant nursing technicains enrolled in the College of Applied Medical Sciences at a public university in Saudi Arabia during the academic year 2021-2022. Data were collected using a self-administered questionnaire that assessed the technicains' knowledge and practices related to patient safety. Descriptive and inferential statistics were used to analyze the data. Results: The overall mean score for knowledge of patient safety was 78.5% (SD = 13.2%), while the overall mean score for practices related to patient safety was 75.6% (SD = 11.8%). There were significant differences in knowledge and practice scores based on the technicains' demographic characteristics, including age, academic year, and previous training on patient safety (p < 0.05). Multiple linear regression analysis revealed that age, academic year, and previous training on patient safety were significant predictors of knowledge and practice scores (p < 0.05). Conclusion: Health assistant nursing technicains in Saudi Arabia have good knowledge and adequate practices related to patient safety. However, there are areas where their knowledge and practices can be improved, particularly in medication safety and error reporting. Nursing education programs should integrate patient safety concepts and best practices into their curricula and provide technicains with hands-on training and clinical experiences to enhance their patient safety competencies. Keywords: patient safety, health assistant nursing technicains, knowledge, practices, Saudi Arabia